Nonlocal Telegraph Equation in Frame of the Conformable Time-Fractional Derivative - Mohamed Bouaouid; Khalid Hilal; Said Melliani (Advances in Mathematical Physics)
We use the cosine family of linear operators to prove the existence, uniqueness, and stability of the integral solution of a nonlocal telegraph equation in frame of the conformable time-fractional derivative. Moreover, we give its implicit fundamental solution in terms of the classical trigonometric functions.